PENDIDIKAN KARAKTER PERSPEKTIF ABDULLAH NASHIH ULWAN (Tinjauan Kitab Tarbiyatul Aulad Fil Islam dan Relevansinya dengan Pendidikan Nasional) - Nur Syarifuddin; M. Fauzi (Akademika, 2019)
It is in need of a right concept that is in accordance with the level of child development, more specifically the concept that is able to shape the child into a Muslim person. The concept of character education in the frame of religious values a purposeful step that can be used as a form of response in facing the challenges of the times. In order to realize a generation that has a strong character, faith and Islam, it is necessary to instill personality values to children. Therefore we need the concept of character education in children. Based on Abdullah Nashih Ulwan's perspective described in this research, it could be concluded that the most influential concept of character education is education by example, education through habituation, education through advice, education through attention and education through punishment.